Learn your Mac : Mac video training - Garay, Paul (Peachpit Press, 2010)
"A Complete and thorough Guide to Your Mac. Let MacVideoTraining.com make your transition as easy as possible with our expert video tutorials that show you the how-to's of using Mac OS X Snow Leopard. Our Mac OS X Basics section will teach you how to navigate your way around Apple's state-of-the-art operating system like a pro. Find files, cut-copy-paste, setup and use printers, hard drives, etc."--Resource description page.